Omega‐3 Polyunsaturated Fatty Acids Inhibit IL‐17A Secretion through Decreased ICAM‐1 Expression in T Cells Co‐Cultured with Adipose‐Derived Stem Cells Harvested from Adipose Tissues of Obese Subjects - Chehimi, Marwa; Ward, Robert; Pestel, Julien; Robert, Maud; Pesenti, Sandra; Bendridi, Nadia; Michalski, Marie‐Caroline; Laville, Martine; Vidal, Hubert; Eljaafari, Assia (Molecular nutrition & food research, 2019)
Scope Obese adipose tissue (AT) is infiltrated by inflammatory immune cells including IL‐17A‐producing‐T (Th17) cells. It has been previously demonstrated that adipose‐derived stem cells from obese (ob‐ASCs), but not lean AT promote Th17 cells. Because n‐3 PUFAs are known to inhibit obese AT inflammation, it is tested here whether they could inhibit ob‐ASC‐mediated IL‐17A secretion. Methods and Results The n‐3 PUFA precursor, alpha‐linolenic acid (ALA), or its derivatives, eicosapentaenoic, or docosahexaenoic acid, is added to co‐cultures of human ob‐ASCs and mononuclear cells (MNCs). All three inhibited IL‐17A, but not IL‐1β, IL‐6, nor TNFα  secretion. As a control, palmitic acid (PA), a saturated fatty acid, did not inhibit IL‐17A secretion. ALA also inhibited IL‐17A secretion mediated by adipocytes differentiated from ob‐ASCs. Toll‐like‐receptor 4 is shown to be involved in ob‐ASC‐mediated‐IL‐17A secretion, and to be inhibited by ALA, together with Cyclo‐Oxygenase‐2 and Signal‐Transducer‐and‐Activator‐of‐transcription‐3. In addition, ALA down‐regulated Intercellular‐Adhesion‐Molecule‐1 (ICAM‐1) expression in both monocytes and ASCs, which resulted in decreased interactions between ob‐ASCs and MNCs, and inhibition of IL‐17A secretion. Conclusion It is demonstrated herein that ALA inhibits Th17 cell promotion, through decreased ICAM‐1expression in both ob‐ASCs and monocytes. This novel mechanism may contribute to explain the beneficial effects of n‐3 PUFA in IL‐17A‐related inflammatory pathologies. n‐3 PUFAs decrease ASC‐mediated IL‐17 A secretion, through ICAM‐1 inhibition of expression. ASCs isolated from obese, but not lean adipose tissue (AT) are previously shown to promote Th17 cells, activate IL‐1β and IL‐6 secretion, and inhibit Th1 cells. Here, it is demonstrated that n‐3PUFAs inhibit ICAM‐1‐mediated cell interactions between ASCs and mononuclear cells, which results in inhibition of IL‐17A secretion.